MOLECULAR CHARACTERIZATION OF BETA THALASSEMIA MAJOR IN PUNJAB, PAKISTAN - Tanveer, Muhammad Irtza; Farzand, Sadaf; Manzoor, Areeba; Anwar, Ambereen; Farhan, Saima; Moin, Saira (Journal of Ayub Medical College Abbottabad, 2026)
Abstract Background: β-Thalassemia major is among the most prevalent hereditary blood disorders in Pakistan. A person develops β-Thalassemia major when they inherit two mutated alleles for the HBB gene. This study aimed to identify the profile of mutations that are found in the population of Punjab, Pakistan, to develop a mutation-targeted diagnostic panel for the detection and better control of the disease. Settings and Method: The study was conducted at the Sundas Foundation. A cross-sectional approach was adopted for this study, and a non-probability consecutive sampling technique was employed to recruit data from 133 patients between January 2023 and December 2024. Blood samples from the patients were collected and tested using Multiplex ARMS-PCR for common and rare HBB mutations in Punjab. Results: Our findings revealed that homozygosity was found in 70.9 % of the cases and compound heterozygosity in the remaining 20.4%. Among the 13 mutations involved in our study: IVS1-5 (G>C) (33.8%), Fr8-9 (+G) (28.6%), Fr41-42 (-CTTT) (15%), IVS1-1 (G>A) (7.1%). These four mutations were common and accounted for 77.5% of the cases. Less commonly encountered mutations involved Codon5 (-CT), Codon15 (A>T), Codon30 (G>C), Cap+1 (A>C), Del619, Fr16 (-C). Three hemoglobin variants- HbE Cd-26, HbS Cd-6, and HbC Cd-6 were also investigated in this study. Conclusion: The most frequently found mutation in our study population is IVS1-5 (G>C). Many additional mutations, such as IVS1-1 (G>A), Fr8-9 (+G), and Fr41-42 (-CTTT), contributed significantly to the disease burden